Transformationen attributiver Genitivkonstruktionen als linguistisches und translationswissenschaftliches Problem im Bereich Leichte Sprache.: Eine kritische Betrachtung der Regelwerke vor dem Hintergrund der neuesten Studienergebnisse - Ziegenhagen, Jonathan (Linguistik Online, 2025)
Translation of the source texts in standard language into the target texts in German Easy Read proves to be a complex scientific issue in the translation studies. This paper examines a specific problem – the substitution of the genitive by the dative constructions – prescribed by official guidelines and linguistic research. It critically analyses related studies in order to draw theoretical conclusions for the practice of Easy Read.